ANALYSIS OF ENGAGEMENT STRATEGY AND MEDIA FEATURES ON CREATIVE BUSINESS GROWTH THROUGH BRAND IMAGE ON MEDAN CITY'S CULINARY DELIGHTS - Bunga Aditi (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2023)
The culinary business is quite promising in the city of Medan, this is indicated by the many offers made by business actors to make this business one of the images to increase profits. The development of the culinary business is increasingly able to provide the best image. The culinary business process has begun to create a strategy through engagement and media features. The purpose of this study is to examine and analyze Engagement and Media Features on Brand Image in increasing the creative economy in Medan's culinary specialties. This study uses data analysis methods using software and SmartPLS. The results of the study show that Engagement and media features have a significant effect on brand image. Engagement and media features have a significant effect on business growth. Brand image has a significant effect on the growth of creative businesses. Brand image as an intervening variable has a significant impact on increasing the influence of Engagement and media features on the growth of creative businesses.